ANALISIS DAMPAK TAMBANG EMAS TRADSIONAL TERHADAP LINGKUNGAN FISIK DAN SOSIAL EKONOMI MASYARAKAT DI DESA POKLA, BUPER – WAENA, KABUPATEN HERAM, JAYAPURA PROVINSI PAPUA - Alfrida Milka Yaru; Mujiati Mujiati; Thobby Wakarwamu (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2022)
Traditional gold mining in Pokla Buper Village, Waena Village, Heram District, Jayapura City, Papua Province has been carried out since 1996, using simple equipment, namely hoes, cauldrons and sieves. In 2010 the mine grew to a large size using a spray method alkon machine. From 2020 to 2022 using heavy equipment, namely excavators and dompeng machines. Factors that trigger the emergence of gold mining, to meet the economic needs of the family and create jobs for the community. The purpose of this study was to analyze the impact of traditional gold mining on the physical environment, socio-economic community and efforts to reduce the negative impact of traditional gold mining. Primary data from observations, interviews and documentation are from respondents who own customary rights, communities living around mining areas, RW heads and employees. The analysis used is descriptive qualitative. The results showed that the impact of traditional gold mining on the physical environment damaged the mining area and landslides occurred in the campus area of the Institute of Domestic Government. The social impact of the community is in the form of a positive impact in the field of education because with education they can build an advanced society. The economic impact of the community can be more independent in managing the potential of existing natural resources. Efforts to reduce the negative impact of traditional gold mining activities are land reclamation of damaged mining areas so that they can function optimally, and develop positive impacts for the community around the mining area.